2020
DOI: 10.1111/jocn.15209
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers' lived experiences of caring for epidermolysis bullosa patients: A phenomenological study

Abstract: Aims and objectives:To explore the lived experiences of family caregivers of epidermolysis bullosa (EB) patients.Background: Patients with EB need long-term care. Their family experiences physical and mental stress while proving that care. However, very little research has explored the family caregivers' actual lived experiences when caring for EB patients.Design: This is a qualitative research using the phenomenological approach.Methods: Data were collected with the assistance of the Taiwan Foundation for Rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(103 citation statements)
references
References 24 publications
5
88
0
10
Order By: Relevance
“…At peak times of the epidemic, severe COVID-19 patients need to be hospitalized. Patients without underlying disease and with mild to moderate severity COVID-19 disease are recommended to be cared for at home by informal caregivers (WHO, 2020; Y. H. Wu, Sun, & Lee, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At peak times of the epidemic, severe COVID-19 patients need to be hospitalized. Patients without underlying disease and with mild to moderate severity COVID-19 disease are recommended to be cared for at home by informal caregivers (WHO, 2020; Y. H. Wu, Sun, & Lee, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature indicated that only one study qualitatively explored the experience of FCs of relatives with COVID-19 and suggested the importance of evaluating the mental health of FCs with a quantitative study (Y. H. Wu et al, 2020 ). FCs face many challenges such as unmet needs, unpleasant physical, psychiatric, and social during caring for their COVID-19 relatives (Y. H. Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…98 There were only 2 studies of interventions (daily walking and yoga) 42,47 to improve physical health in this population, despite recognition that public health initiatives may need to be modified for caregivers. 22 Smoking, Drinking, and Drug Use Authors of 12 studies explored coping behaviors detrimental to health, including self-harm, 87 the use of alcohol, 45,92,101,104,105 illicit drugs, 92,101,105 and tobacco. 92,100,105 Use of alcohol, illicit drugs, and tobacco were explored as coping mechanisms, but the studies did not elaborate on the frequency of use, and no studies reported on interventions to reduce these behaviors.…”
Section: Sleepmentioning
confidence: 99%
“…14,47,77,78,85 The remaining quantitative studies measured caregiver's health using other questionnaires, activity trackers, or cortisol. Of them, 19 studies 15,[42][43][44][45][46]50,83,[86][87][88][89][90][91][92][93][94][95][96] demonstrated that the physical health of caregivers who care for a child with a LLC or LTI was negatively affected.…”
mentioning
confidence: 99%
See 1 more Smart Citation